Direct dioxygen evolution in collisions of carbon dioxide with surfaces - Yunxi Yao (Nature Portfolio, 2019)
Carbon dioxide can dissociate via different pathways depending on the amount of available energy. Here the authors investigate carbon dioxide collisions with metal substrates and observe a pathway producing molecular oxygen, which might explain the presence of oxygen in abiotic environments.